PEMANFAATAN LITERASI PENDIDIKAN KARAKTER DALAM MELAKSANAKAN PERAN PENDIDIK ANAK DI USIA DINI - Mallapiang, Yassir; Sujariati, Sujariati; Ratna Dewi, Erni; Qalbi, Nur Qalbi; Samudi, Samudi (TONGKONAN: JURNAL PENGABDIAN MASYARAKAT, 2023)
This training has done in Jagong district of Pangkep regency Sulawesi-selatan. This training goals to educate the society how to educate the character of children under the 17 th age. . The training also aims to gaining the parent tobe sensitive to event factual dealt with nauthiness’ adult as young generation. This training has done around a day by some lecturers from Adpertisi institute of Makassar. And the result achievement was good responses and practice actively from the participant by giving feed back as questions and also doing sharing session about their children at home and how to educate them well, how to applied communicating to children in every activity at home.